COVID-19 and New Forms of Acute Pneumonia. It's Time for A Brainstorming Session - Igor, Klepikov (International Journal of Coronaviruses, 2020)
This perspective calls for cross‑disciplinary brainstorming on novel COVID‑19 pneumonia phenotypes. It discusses hypotheses on immune dysregulation, microvascular injury, and tailored respiratory strategies.
Keywords: Covid-19